Ethics Adviser, Means Who? - Świeszczak, Marika; Świeszczak, Krzysztof (Journal of Finance and Financial Law, 2016)
The problem of ethics is particularly important for banks, because on moral principles they base their activity, customer relations and other functional areas, such as the policy of dividend payments, the mission of the institution, responsibilities of employees, etc. The question is whether the banks cannot afford to waive of these rules for the benefit (even disposable)? Advisor is the first link and therefore he is particularly important in the context of building ethics policy and implementation of ethical values. The perception of employees affects the image of the bank and its reputation, which is why it is so essential that consumers regard them as operating in accordance with the rules of ethics. The aim of the article is to present the work of bank advisor from the perspective of ethical principles and to present the results of a pilot study about the understanding of the concept of ethics and ethical advisor as well as associations with the term bank.